2013
DOI: 10.1111/head.12081
|View full text |Cite
|
Sign up to set email alerts
|

Atypical Resting‐State Functional Connectivity of Affective Pain Regions in Chronic Migraine

Abstract: Objective Chronic migraineurs (CM) have painful intolerances to somatosensory, visual, olfactory and auditory stimuli during and between migraine attacks. These intolerances are suggestive of atypical affective responses to potentially noxious stimuli. We hypothesized that atypical resting state functional connectivity (rs-fc) of affective pain processing brain regions may associate with these intolerances. This study compared rs-fc of affective pain processing regions in CM to controls. Methods Twelve minut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
155
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 175 publications
(170 citation statements)
references
References 87 publications
15
155
0
Order By: Relevance
“…Resting-state functional connectivity studies have shown that compared with healthy controls, people with migraine have stronger connectivity between affective-motivational brain regions and those responsible for sensory-discriminative processing. For example, studies demonstrate that people with migraine have stronger connectivity between anterior insula with primary visual cortex, primary auditory cortex and thalamus, and between amygdala with visceroceptive insular cortex, auditory cortex, thalamus and somatosensory cortex 89 91 93. Stronger functional connectivity could predispose the person with migraine to greater emotional responses to noxious sensory stimuli during the migraine attack.…”
Section: Knowledge Learned From Imaging Studies: How Functional Imagimentioning
confidence: 99%
“…Resting-state functional connectivity studies have shown that compared with healthy controls, people with migraine have stronger connectivity between affective-motivational brain regions and those responsible for sensory-discriminative processing. For example, studies demonstrate that people with migraine have stronger connectivity between anterior insula with primary visual cortex, primary auditory cortex and thalamus, and between amygdala with visceroceptive insular cortex, auditory cortex, thalamus and somatosensory cortex 89 91 93. Stronger functional connectivity could predispose the person with migraine to greater emotional responses to noxious sensory stimuli during the migraine attack.…”
Section: Knowledge Learned From Imaging Studies: How Functional Imagimentioning
confidence: 99%
“…5,6 Other studies used region-of-interest (ROI) analysis, focusing on pain-related regions such as the periaqueductal gray or amygdala and found increased connectivity in these networks. [7][8][9] Still others have used differences identified with voxel-based morphometry to seed ROI-based connectivity studies. [10][11][12][13] This approach has identified differences between females and males in cortical thickness and connectivity of the posterior insula and precuneus.…”
Section: 3mentioning
confidence: 99%
“…responsivity to sensory stimuli [26,43,44] % cortical thickness and activation S1, temporal lobe ! insula, cingulate [26] % rs connectivity limbic areas (Am, Ins, ACC)-thalamus, PAG, midtemporal, entorhinal, S1 [131] ! rs connectivity caudate-insula; % putamen-insula [132] % activation dorsolateral pons [47] %% iron content PAG and globus pallidus (T2) [29,31] !…”
Section: Episodic Migraine (Interictal)mentioning
confidence: 99%